Graft-Versus-Lymphoma Effect in Relapsed Peripheral T-Cell Non-Hodgkin's Lymphomas After Reduced-Intensity Conditioning Followed by Allogeneic Transplantation of Hematopoietic Cells - Paolo Corradini; Anna Dodero; Francesco Zallio; Daniele Caracciolo; Marco Casini; Marco Bregni; Franco Narni; Francesca Patriarca; Mario Boccadoro; Fabio Benedetti; Alessandro Rambaldi; Alessandro M. Gianni; et al. (2004)
Purpose Peripheral T-cell lymphomas (PTCLs) are a heterogeneous group of malignancies characterized by a poor prognosis. We performed a pilot study to investigate the role of reduced-intensity conditioning (RIC) followed by allogeneic stem-cell transplantation in relapsed or refractory PTCLs. Patients and Methods We have conducted a phase II trial on 17 patients receiving salvage chemotherapy followed by RIC and allogeneic transplantation of hematopoietic cells. The RIC regimen consisted of thiotepa, fludarabine, and cyclophosphamide. The acute graft-versus-host disease prophylaxis consisted of cyslosporine and short course methotrexate. Results Patients had a median age of 41 years (range, 23 to 60 years). Two patients were primary chemorefractory, and 15 had relapsed disease; eight patients (47%) had a disease relapse after an autologous transplantation. After a median follow-up of 28 months from the day of study entry (range, 3 to 57 months), 14 of 17 patients were alive (12 in complete remission, one in partial remission, and one with stable disease), two died as a result of progressive disease, and one died as a result of sepsis concomitant to acute graft-versus-host disease. The estimated 3-year overall and progression-free survival rates were 81% (95% CI, 62% to 100%) and 64% (95% CI, 39% to 89%), respectively. The estimated probability of nonrelapse mortality at 2 years was 6% (95% CI, 1% to 17%). Donor lymphocyte infusions induced a response in two patients progressing after allografting. Conclusion RIC followed by allogeneic stem-cell transplantation is feasible, has a low treatment-related mortality, and seems to be a promising salvage treatment for relapsed PTCL. These findings suggest that the existence of a graft-versus-T-cell lymphoma effect.